'Who wants left-wing policies? Economic preferences and political cleavages in Turkey'. Issue 1 (1st January 2023) - Yagci, Alper H.; Harma, Mehmet; Tekgüç, Hasan
ABSTRACT: We administer a survey of economic policy preferences to a representative sample of the Turkish voting-age population. We show that policy preferences are distributed in non-linear ways that are at odds with what could be expected from a conventional left-right division. We find that while objective socioeconomic differences are bad at predicting economic policy preferences, the latter are distinctly associated with politically salient cleavages built on religiosity and ethnicity. We also examine how preferences of each party's voters compare with party programmes.